Analisis Implementasi Masterplan Industri Halal Indonesia: Studi Konten Media - Emma Atmawati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study explores the implementation of the Indonesian Halal Industry Masterplan (MPIHI) 2023-2029 and analyzes the various challenges faced, including regulatory constraints, infrastructure, and collaboration between stakeholders. This study uses the content analysis method as the main approach to examine the implementation of the Indonesian Halal Industry Masterplan (MPIHI) 2023–2029. The results of this study found that although MPIHI has great potential to make Indonesia the center of the world's halal industry, there is still a gap between the policies designed and the actual conditions on the ground. Therefore, this study offers a number of recommendations to improve the effectiveness of MPIHI implementation, so that it can make a real contribution to the growth of Indonesia's halal economy.